Cross-Cultural Ethnobotanical Assembly as a New Tool for Understanding Medicinal and Culinary Values–The Genus Lycium as A Case Study - Yao, Ruyu; Heinrich, Michael; Wei, Jianhe; Xiao, Peigen (Frontiers in Pharmacology, 2021)
Ethnobotanical knowledge is indispensable for the conservation of global biological integrity, and could provide irreplaceable clues for bioprospecting aiming at new food crops and medicines. This biocultural diversity requires a comprehensive documentation of such intellectual knowledge at local levels. However, without systematically capturing the data, those regional records are fragmented and can hardly be used. In this study, we develop a framework to assemble the cross-cultural ethnobotanical knowledge at a genus level, including capturing the species’ diversity and their cultural importance, integrating their traditional uses, and revealing the intercultural relationship of ethnobotanic data quantitatively. Using such a cross-cultural ethnobotanical assembly, the medicinal and culinary values of the genus Lycium are revealed, in the meanwhile, it highlights the problems and options for a systematic cross-cultural ethnobotanical knowledge assembly. The framework used here could generate baseline data relevant for conservation and sustainable use of plant diversity as well as for bioprospecting within targeting taxa.